Sociological imagination to study youths - Canales Cerón, Manuel; Duarte Quapper, Klaudio (Última Década, 2020)
In sociology, there is a particular emphasis on the relevance of W. Mills’ contributionwith his proposal of the sociological imagination as a way to display knowledge insociety and to elaborate its transformation alternatives. In the present conversation, theChilean sociologist Manuel Canales Cerón reflects on the ways in which the denseobservation of youth dynamics in diverse historical processes allows such kind ofunderstanding of social matters. In order to achieve it, Canales connects his ownbiography as a sociology student, as an educator inside working-class neighborhoodsduring dictatorship, and as a social scientist today, joining his life story, historical contextand structural conditions throughout his reflection; all these three dimensions aresimultaneously the three dimensions he applies in his job in order to analyze youthrelated matters critically, and the three dimensions supporting the proposal ofsociological imagination.